Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1365-2249.2004.02447.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary immune response to keyhole limpet haemocyanin following trauma in relation to low plasma glutamine

Abstract: SUMMARYSevere trauma can lead to a compromised immune response, thereby increasing susceptibility to infections. Here we will study to what extent these early changes in the immune status upon trauma affect a primary immune response to keyhole limpet haemocyanin (KLH). Because glutamine is the preferred respiratory substrate for immune competent cells and known to be depleted after trauma, we studied the immune status and the primary sensitization in relation to the glutamine plasma concentration in a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…In their study concerning immuno toxicity Roth et al have shown that only the levels of KLH specific antibodies have been elevated in the group, immunized with KLH (50 mg/rat in aluminium hydroxide) compared to the control nontreated animals and there was no detectable difference between them in the following parameters: number CD4þ cells and lymphocyte count; development of germinal centers in Axillary lymph nodes and macrophage accumulation and granuloma formation/capsule in the site of the injection [26]. Boelens et al, examine the antibody response to KLH in healthy and trauma patients and did not find neither in the patients nor in the healthy controls anti KLH antibodies of the IgE-isotype [27].…”
Section: Discussionmentioning
confidence: 97%
“…In their study concerning immuno toxicity Roth et al have shown that only the levels of KLH specific antibodies have been elevated in the group, immunized with KLH (50 mg/rat in aluminium hydroxide) compared to the control nontreated animals and there was no detectable difference between them in the following parameters: number CD4þ cells and lymphocyte count; development of germinal centers in Axillary lymph nodes and macrophage accumulation and granuloma formation/capsule in the site of the injection [26]. Boelens et al, examine the antibody response to KLH in healthy and trauma patients and did not find neither in the patients nor in the healthy controls anti KLH antibodies of the IgE-isotype [27].…”
Section: Discussionmentioning
confidence: 97%
“…KLH is recognised as a potent stimulator of T dependant humoral responsiveness and has been used to test immune function in many clinical situations, including severely traumatised patients [28]. There were robust antibody responses (IgM and IgG) against KLH in all treatment groups following boosting with that antigen.…”
Section: Discussionmentioning
confidence: 98%
“…Trauma and major burns have been reported to result in diminished production of IL‐12, reduced Th1 responses, and decreased resistance to infection 10–21. IL‐12 has multiple biologic effects on T‐cell and natural killer (NK) cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with traumatic open fractures or other serious injuries are vulnerable to infections, and it is generally agreed that the decreased resistance to infection is associated with abnormalities of both natural and adaptive immunity. Among those abnormalities is the loss of function of the T helper 1 (Th1) lymphocyte phenotype 10–21. Because Th1 cells are principal regulators of cell‐mediated immune response and the production of complement‐fixing antibodies,22 depressed function of this lymphocyte subset is believed to be related to reduced resistance to infection in injured patients 12, 16, 19, 21.…”
mentioning
confidence: 99%